Productivity effects of basic research in low-tech and high-tech industries - Dirk Czarnitzki; Susanne Thorwarth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
R&D encompasses plenty of activities which are usually summarized under the terms of basic research, applied research and development. Although basic research is often associated with low appropriability it provides the fundamental basis for subsequent applied research and development. Especially in the high-tech sector basic research capabilities are an essential component for a firm's success. We use firm-level panel data stemming from Belgian R&D surveys and apply a production function approach which shows that basic research exhibits a premium on a firm's output when compared to applied research and development. When we split the sample into high-tech and low-tech companies, we find a large premium of basic research for firms in high-tech industries, but no premium in low-tech sectors.
urn:nbn:de:bsz:180-madoc-322436
Keywords: L23; O30; O33; 330; Basic Research; R&D; Production Function Estimation; Grundlagenforschung; Industrielle Forschung; Produktivität; Produktionsfunktion; Schätzung; Belgien